Independent impacts of age and hearing loss on spatial release in a complex auditory environment - Gallun, Frederick J.; Diedesch, Anna C.; Kampel, Sean D.; Jakien, Kasey M. (Frontiers in Neuroscience, 2013)
Listeners in complex auditory environments can benefit from the ability to use a variety of spatial and spectrotemporal cues for sound source segregation. Probing these abilities is an essential part of gaining a more complete understanding of why listeners differ in navigating the auditory environment. Two fundamental processes that can impact the auditory systems of individual listeners are aging and hearing loss. One difficulty with uncovering the independent effects of age and hearing loss on spatial release is the commonly observed phenomenon of age-related hearing loss. In order to reveal the effects of aging on spatial hearing, it is essential to develop testing methods that reduce the influence of hearing loss on the outcomes. The statistical power needed for such testing generally requires a larger number of participants than can easily be tested using traditional behavioral methods. This work describes the development and validation of a rapid method by which listeners can be categorized in terms of their ability to use spatial and spectrotemporal cues to separate competing speech streams. Results show that when age and audibility are not covarying, age alone can be shown to substantially reduce spatial release from masking. These data support the hypothesis that aging, independent of an individual’s hearing threshold, can result in changes in the cortical and/or subcortical structures essential for spatial hearing.